2007
DOI: 10.1534/genetics.106.068361
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait loci and Environmental Interactions for Accumulation and Remobilization of Water-Soluble Carbohydrates in Wheat (Triticum aestivum L.) Stems

Abstract: Genetic analyses of nine traits associated with stem water-soluble carbohydrate (SWSC) accumulation and remobilization at grain-filling period under drought stress (DS) and well-watered (WW) conditions were undertaken using doubled haploid lines (DHLs) derived from two Chinese common wheat cultivars. Some significantly and very significantly positive correlation was observed among nine traits associated with SWSC. Higher phenotypic values for most traits were detected under DS. Broad sense heritabilities (h 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 46 publications
12
117
1
1
Order By: Relevance
“…According to Rebetzke et al (2007), the QTL on chromosome 2D was also mapped for WSC. It was also supported by Yang et al (2007), but they reported QTL for WSC away from those markers that we found, and also it was reported at flowering stage. Dodig et al (2012) identified SSR marker Xgwm484 (41 cM) for chlorophyll content at grain filling but far distance from that marker we reported.…”
Section: Chromosome 2dsupporting
confidence: 89%
See 3 more Smart Citations
“…According to Rebetzke et al (2007), the QTL on chromosome 2D was also mapped for WSC. It was also supported by Yang et al (2007), but they reported QTL for WSC away from those markers that we found, and also it was reported at flowering stage. Dodig et al (2012) identified SSR marker Xgwm484 (41 cM) for chlorophyll content at grain filling but far distance from that marker we reported.…”
Section: Chromosome 2dsupporting
confidence: 89%
“…The distance among these markers were less than 10 cM. Yang et al (2007) detected QTL with flanking marker of Xwmc524~Xgwm595 for TGWG, it was on the same chromosome as our studies but with different position and also was associated with same trait as in this study. Furthermore, (Maccaferri et al, 2011) found Xbarc197 located on chromosome 5A (53 cM) adjacent with Xgwm293 (52 cM) and also nearby Xgwm415 and Xgwm304 (56 and 61 cM apart), was associated with grain yield using association analysis.…”
Section: Chromosome 5asupporting
confidence: 73%
See 2 more Smart Citations
“…Water-soluble carbohydrates are important for maintaining grain size, particularly under drought conditions when photosynthesis is arrested (Gebbing et al 1999;Yang et al 2001;Ruuska et al 2006Ruuska et al , 2008. Genetic variation in the ability to mobilise stem reserves to the developing grain has been identified and used for biochemical characterisation and QTL mapping (Yang et al 2007;Ehdaie et al 2008;Xue et al 2008). The staygreen trait, which is characterised by delayed leaf senescence, is generally considered to improve tolerance at the vegetative stage to mid-season droughts (Thomas and Howarth 2000), but the trait may also interfere with carbohydrate mobilisation to the reproductive structures and affect grain-filling (Blum 1998; Sanchez et al 2002;Collins et al 2008;Blum 2011).…”
Section: Vegetative Versus Reproductive Stage Abiotic Stressesmentioning
confidence: 99%